PEMBELAJARAN KOOPERATIF DENGAN STRATEGI ”KARMIN ALJABAR” MENRAMPILKAN OPERASI HITUNG ALJABAR - Heru Wahyudi (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2020)
Abstract: The implementation of learning is expected to be active, innovative, creative, and fun without leaving the learning concepts. Calculating algebra is a very important learning and many students have difficulty. From the researcher's experience, learning algebra by utilizing the algebra domino card has an impact on students' interest in learning but learning outcomes don’t meet the completeness standards. Researchers strive for more interesting learning by giving deeper concepts in the learning process through cooperative learning with a contextual approach assisted by an Algebra Domino Card, which called